A CROSS-REFERENCE OF MEDICAL TERMS (Центральноазиатский журнал образования и инноваций, 2024)
Medical term or language plays a vital role in a wide variety of disciplines such as medicine, clinical pharmacy, medical engineering, nursing, healthcare management, the academic training, zoological sciences, animal healthcare medicine and public health epidemiology but not limited to those outlined above. While the acquisition of this language is paramount to the study of medicine and related disciplines, it is worthwhile to understand the key underlying principles that constitute the formation of these terms such as prefixes, suffixes, combining form, English vowel-O, adjective makers, and word roots. In this article, the author aims at highlighting and explaining how these principles or rules if properly followed can lead to successful medical language acquisition hereto refers to as medical terminology.